Tailor-made spider-eggcase-silk spheres for efficient lysosomal drug delivery. Issue 17 (6th March 2018) - Chen, Jianming; Hu, Jinlian; Zuo, Peijun; Su, Xiaoqian; Liu, Zhigao; Yang, Mo
Abstract : Recombinant spider-eggcase-silk spheres are facilely prepared as drug carriers with a tailor-made isoelectric point specifically for lysosomal delivery. Abstract : Spider silks are attractive biopolymers due to their excellent mechanical properties and biomimetic potential. To optimize the electrostatic interaction for lysosomal drug delivery, a spider-eggcase-silk protein was genetically engineered using 5× His Tag with a tailor-made isoelectric point of 4.8. By a facile HFIP-on-oil method, silk spheres were assembled as rapidly as 10 s. After the post-treatment of ethanol, silk spheres were determined with an improved compressive modulus by AFM indentation. Under incubation of silk spheres in a Doxorubicin solution, a maximum of 35% loading and average of 30% loading efficiency were determined. In the cytotoxicity experiment, silk spheres exhibited intrinsic biocompatibility and showed good control of the loaded drug in the neutral PBS solution. Significantly, by 96 h, the accumulative drug release at pH 4.5 was approximately 4.5-fold higher than that at pH 7.4. By conducting the platelet adhesion and hemolysis assay, Doxorubicin-loaded silk spheres exhibited good hemocompatibility. To further demonstrate this release behavior, within 24 h, Doxorubicin-loaded silk spheres were efficiently delivered to lysosomes and then released the payload to the nuclei of Hela cells.